GERMANIUM ISOTOPIC VARIATIONS IN IGNEOUS ROCKS AND MARINE SEDIMENTS - Rouxel O.; Galy A.; Elderfield H. (My University, 2006)
A new technique for the precise and accurate determination of Ge stable isotope compositions has been developed and applied to silicate rocks and biogenic opal. The analyses were performed using a continuous flow hydride generation system coupled to a MC-ICPMS. Samples have been purified through anion- and cation-exchange resins to separate Ge from matrix elements and eliminate potential isobaric interferences. Variations of 74Ge/70Ge ratios are expressed as δ74Ge values relative to our internal standard and the long-term external reproducibility of the data is better than 0.2‰ for sample size as low as 15 ng of Ge. Data are presented for igneous and sedimentary rocks, and the overall variation is 2.4‰ in δ74Ge, representing 12 times the uncertainty of the measurements and demonstrating that the terrestrial isotopic composition of Ge is not unique. Co-variations of 74Ge/70Ge, 73Ge/70Ge and 72Ge/70Ge ratios follow a mass-dependent behaviour and imply natural isotopic fractionation of Ge by physicochemical processes. The range of δ74Ge in igneous rocks is only 0.25‰ without systematic differences among continental crust, oceanic crust or mantle material. On this basis, a Bulk Silicate Earth reservoir with a δ74Ge of 1.3 ± 0.2‰ can be defined. In contrast, modern biogenic opal such as marine sponges and authigenic glauconite displayed higher δ74Ge values between 2.0‰ and 3.0‰. This suggests that biogenic opal may be significantly enriched in light isotopes with respect to seawater and places a lower bound on the δ74Ge of the seawater to +3.0‰.This suggests that seawater is isotopically heavy relative to Bulk Silicate Earth and that biogenic opal may be significantly fractionated with respect to seawater. Deep-sea sediments are within the range of the Bulk Silicate Earth while Mesozoic deep-sea cherts (opal and quartz) have δ74Ge values ranging from 0.7‰ to 2.0‰. The variable values of the cherts cannot be explained by binary mixing between a biogenic component and a detrital component and are suggestive of enrichment in the light isotope of diagenetic quartz. Further work is now required to determine Ge isotope fractionation by siliceous organisms and to investigate the effect of diagenetic processes during chert lithification.
Keywords: Germanium isotope; igneous rocks; marine sediments